2017
DOI: 10.1097/md.0000000000006332
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and clinical characteristics by gender differences in patients with Kikuchi–Fujimoto disease

Abstract: Kikuchi–Fujimoto disease (KFD) is a rare, self-limiting disorder that typically affects the cervical lymph nodes (LNs). Although initially described in young women, KFD also occurs in men. There are no reports on the clinical manifestations and characteristics of male KFD patients. Therefore, this study was conducted to assess the incidence of KFD among males, as well as the most frequent clinical characteristics of these patients. A retrospective, cross-sectional study was performed at a tertiary hospital of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
(27 reference statements)
2
15
0
Order By: Relevance
“…There is a large Korean study of 254 patients by Jung et al that suggested gender differences in clinical and laboratory manifestation 10. In the study, women were more likely to have autoimmune features and positive ANA, while men were more likely to have fever, headache, bilateral lymphadenopathy, thrombocytopaenia, raised CRP, raised LDH and liver derangement.…”
Section: Discussionmentioning
confidence: 94%
“…There is a large Korean study of 254 patients by Jung et al that suggested gender differences in clinical and laboratory manifestation 10. In the study, women were more likely to have autoimmune features and positive ANA, while men were more likely to have fever, headache, bilateral lymphadenopathy, thrombocytopaenia, raised CRP, raised LDH and liver derangement.…”
Section: Discussionmentioning
confidence: 94%
“…2 Most commonly affects young people under 30 years of age, with equal incidence in both sexes. 3 Usually presents as painless cervical lymphadenopathy with constitutional symptoms. Associated hepatomegaly, leukopenia, increased erythrocyte sedimentation rate (ESR), increased liver enzyme levels.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [ 16 ] reported that the development of autoimmune disease was diagnosed in approximately 4% in children with KFD. In an adult study, 7% of KFD patients had autoimmune disease [ 17 ]. Although the exact mechanism by which KFD and other autoimmune disease were related is unknown, but based on laboratory and histological findings, it has been hypothesized that KFD might represent an exuberant T-cell-mediated response to certain antigen stimuli in genetically susceptible individuals [ 14 ].…”
Section: Discussionmentioning
confidence: 99%